2004
DOI: 10.1074/jbc.m404201200
|View full text |Cite
|
Sign up to set email alerts
|

A Proteomic Study of SUMO-2 Target Proteins

Abstract: The SUMO family in vertebrates includes at least three distinct proteins (SUMO-1, -2, and -3) that are added as post-translational modifications to target proteins. A considerable number of SUMO-1 target proteins have been identified, but little is known about SUMO-2. A stable HeLa cell line expressing His 6 -tagged SUMO-2 was established and used to label and purify novel endogenous SUMO-2 target proteins. Tagged forms of SUMO-2 were functional and localized predominantly in the nucleus. His 6 -tagged SUMO-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
167
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(174 citation statements)
references
References 72 publications
(65 reference statements)
5
167
1
1
Order By: Relevance
“…These results indicate that a substantial fraction of the sites seems to be unrelated to proteasomal-mediated degradation and suggests that Ub conjugation to SR proteins may work as a regulatory signal instead of as a degradation labeling (16,49). Likewise, proteomic approaches revealed that RNA-binding proteins are the predominant group among small Ubiquitin-like modifier (SUMO) conjugation substrates, including several hnRNPs, SR family members and spliceosome components (50,51). Furthermore, SUMO conjugation has been found to regulate different aspects of mRNA metabolism such as pre-mRNA 3 0 end processing and RNA editing, by modifying the function of poly(A) polymerase, symplekin and CPSF-73 in the former case and ADAR1 in the latter (52,53).…”
Section: Post-translational Modifications Of Sr Proteins: Above and Bmentioning
confidence: 97%
“…These results indicate that a substantial fraction of the sites seems to be unrelated to proteasomal-mediated degradation and suggests that Ub conjugation to SR proteins may work as a regulatory signal instead of as a degradation labeling (16,49). Likewise, proteomic approaches revealed that RNA-binding proteins are the predominant group among small Ubiquitin-like modifier (SUMO) conjugation substrates, including several hnRNPs, SR family members and spliceosome components (50,51). Furthermore, SUMO conjugation has been found to regulate different aspects of mRNA metabolism such as pre-mRNA 3 0 end processing and RNA editing, by modifying the function of poly(A) polymerase, symplekin and CPSF-73 in the former case and ADAR1 in the latter (52,53).…”
Section: Post-translational Modifications Of Sr Proteins: Above and Bmentioning
confidence: 97%
“…With the long distances that mRNAs and RNA-binding proteins must travel in neurons, sumoylation may provide a means to recycle some proteins to the nucleus by targeting these proteins for retrograde transport. Sumoylation has recently been demonstrated for a few RNAbinding proteins (19)(20)(21)(22). Sumoylation of hnRNP C decreases its nucleic acid binding (21).…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic analyses have demonstrated that the pool of cellular proteins SUMOylated with SUMO1 only partially overlaps the pool of proteins SUMOylated with SUMO2/3 (47)(48)(49). Furthermore, conjugation with SUMO2/3 is known to exert at least one potentially different effect on the target from that exerted by SUMO1 conjugation, namely, the formation of SUMO2/3 chains followed by the recognition of the poly-SUMOylated target by SUMO-dependent ubiquitin ligases that polyubiquitinylate it and direct it toward proteasomal degradation, as previously reviewed (50)(51)(52).…”
Section: Pr8mentioning
confidence: 99%